Descripcion de las ninfas 3, 4 y 5 de Placomerus micans (Heteroptera: Naucoridae) - López Ruf, Mónica Liliana (1996)
Third, fourth, and fifth nymphal instars of P. micans La Rivers are described and illustrated. The use of SEM made it possible to obtain a more detailed knowledge of adults and nymphs of this species and of the Old World species Aphelocheirus aestivalis Fab. This would be a further element to consider in order to analyze the relationships between both genera.